ACTIVATION OF STRUCTURAL PROCESSES OF SMALL TOWN ECONOMY IN CONDITIONS OF DECENTRALIZATION (International Journal of Innovative Technologies in Economy, 2020)
The article is devoted to the study of structural changes in the economy of local urban economic systems of Transcarpathian region in the conditions of deepening of market transformation processes. The main attention is paid to the analysis of structural processes in industrial production and services as priority spheres of management in small towns and urban settlements. The intensity of structural shifts in terms of economic activities is analyzed. An analysis of the dynamics of structural shifts during the analyzed period showed that the most dynamically structural processes occurred in industry, in particular at city-forming industrial enterprises. The activity of small businesses, which today constitute the economic basis of urban settlements, and their impact on urban employment are analyzed.